Analysis Factors Influencing Rice Farmers Poverty of The Family Hope Program (PKH) In Bojonegoro, Indonesia - Ridwan, Awaludin; Indah, Afsah (HABITAT, 2025)
This research was conducted with the aim of analyzing the influence of factors on poverty rice farmers receiving the Family Hope Program in Bojonegoro Regency. Based on the Central Statistics Agency in 2023, the number of poor people in East Java Province was 4188.81 thousand people. Meanwhile, in Bojonegoro Regency in 2023 it was 153.25 thousand people. This indicates that the poverty rate in Bojonegoro Regency is still very high, as evidenced by data from the Bojonegoro Regency Social Service that Kedungadem and Ngraho District have extreme poverty levels. This study uses a quantitative approach. This study used 100 respondents spread across Bojonegoro Regency. The data analysis conducted using a linear probit regression analysis method. The probit analysis method uses dummy variables. This study uses STATA17 software. The analysis results show that factors the poverty factors of households receiving the family hope program in Bojonegoro Regency have a significant influence on the level of head of family, household size, income and production. Based on the research results, efforts that can be made to reduce poverty among recipients of the family hope program among farmers include strengthening relationships, especially among farmers, to help, provide guidance and counseling.